MANAGEMENT OF STRENGTHENING STUDENTS' CHARACTER EDUCATION IN SOCIAL STUDIES LEARNING AT SD NEGERI 23 HALMAHERA WAT - Haryati Lila; Rustam Hasim; Irwan Abbas (SOSIOEDUKASI, 2026)
This study aims to find out how to manage the strengthening of students' character education in Social Science (IPS) learning at SD Negeri 23 West Halmahera. This research uses a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The research informants consisted of school principals, social studies teachers, and several students as supporting sources of information. The results of the study show that the management of strengthening character education is carried out through several stages, namely planning, implementation, and evaluation. Principals and teachers actively design learning strategies that integrate character values, such as honesty, discipline, responsibility, and cooperation, into every social studies learning activity. The implementation of learning is carried out with a variety of methods, including group discussions, simulations, and case studies, so that students can understand character values contextually. Character education evaluation is carried out through observation of student behavior, teacher reflection, and assessment of learning outcomes. Supporting factors for the success of character education management include the commitment of teachers and principals, facility support, and cooperation with parents. Meanwhile, inhibiting factors include limited time, large number of students, and inadequate learning facilities. The conclusion of this study shows that the management of strengthening character education at SD Negeri 23 West Halmahera runs systematically and effectively, despite several obstacles. The integration of character education in social studies learning is able to form students who are disciplined, responsible, and have good social skills.